The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna (Journal of Environmental Science and Health, Part A, 2011)
The aim of this study is to determine the sorption-desorption behavior of a mixture of thirteen aqueous PAHs on cork waste at a particle of size 0.25?0.42 mm obtained from the remains of cork strips. The final purpose is to use this natural adsorbent as an alternative to activated carbon in an innovative approach for the removal of this class of toxic compounds, and significantly reduce the regeneration costs of the process. The chemical composition of the selected cork revealed that suberin (38.5 %) and lignin (31.6 %) were the main structural components of the cell wall. The high efficiency of cork as a biosorbent of PAHs is shown by the fact that just over 80 % of adsorption occurred during the first two minutes of contact time. Both Freundlich's and Langmuir's isotherms gave good fits to the sorption process. The highest adsorption affinities were exhibited for pyrene, anthracene, and phenanthrene. Desorption studies indicate a high degree of irreversibility for all PAHs, and especially so in the case of high molecular PAHs. The correlation with KF and low molecular weight PAHs was the most significant. The quantity of cork required to reduce water pollution was estimated to be between 3 and 15 times less than the quantities required in the case of other materials (i.e. aspen wood and leonardite). This study demonstrates for the first time that cork is a potential biosorbent for PAHs and may have relevance in the future treatment of PAH-contaminated waters.
From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 21644164
Keywords: Adsorption; Aromatic; Aromatic: chemistry; biosorbent; Chemical; Chemical: chemistry; Cork waste; Environmental Remediation; Environmental Remediation: methods; Gas Chromatography-Mass Spectrometry; Lignin; Lignin: chemistry; Lipids; Lipids: chemistry; organic pollutants; PAHs; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Solid Phase Microextraction; sorption-desorption; Time Factors; Water Pollutants; water treatment

Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Penuelas, Josep; Lope-Piedrafita, Silvia (BMC plant biology, 2010)
Drought is a common stressor in many regions of the world and current climatic global circulation models predict further increases in warming and drought in the coming decades in several of these regions, such as the Mediterranean basin. The changes in leaf water content, distribution and dynamics in plant tissues under different soil water availabilities are not well known. In order to fill this gap, in the present report we describe our study withholding the irrigation of the seedlings of Quercus ilex, the dominant tree species in the evergreen forests of many areas of the Mediterranean Basin. We have monitored the gradual changes in water content in the different leaf areas, in vivo and non-invasively, by 1H magnetic resonance imaging (MRI) using proton density weighted (rhow) images and spin-spin relaxation time (T2) maps.
From Duplicate 1 ( Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Peñuelas, Josep; Lope-Piedrafita, Silvia )
Keywords: Droughts; Magnetic Resonance Imaging; Physiological; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus: metabolism; Seedling; Seedling: metabolism; Soil; Soil: analysis; Stress; Time Factors; water; Water: metabolism (citation)

Sensitivity of volatile monoterpene emission to changes in canopy structure: a model-based exercise with a process-based emission model - Grote, Rüdiger (New Phytologist, 2007)
* • This paper investigates the dependence of monoterpene emissions at the canopy scale on total leaf area and leaf distribution. Simulations were carried out for a range of hypothetical but realistic forest canopies of the evergreen Quercus ilex (holm oak). * • Two emission models were applied that either did (SIM-BIM2) or did not (G93) account for cumulative responses to temperature and light. Both were embedded into a canopy model that considered spatial and temporal variations of foliage properties. This canopy model was coupled to a canopy climate model (CANOAK) to determine the micrometeorological conditions at the leaf scale. * • Structural properties considerably impacted monoterpene emission. The sensitivities to changes in total leaf area and to leaf area distribution were found to be of similar magnitude. The two different models performed similarly on a whole-year basis but showed clear differences during certain episodes. * • The analysis showed that structural indices have to be carefully evaluated for proper scaling of emission from leaves to canopy. Further research is encouraged on seasonal dynamics of emission potentials.
Keywords: Biological; biomass; foliage distribution; leaf area index; light; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: radiation effects; Plant Leaves; Plant Leaves: metabolism; Plant Leaves: radiation effects; Quercus; Quercus ilex; Quercus: metabolism; Quercus: radiation effects; Scaling; stand density; Temperature; Time Factors; Volatilization

Folk phytotherapeutical plants from Maratea area (Basilicata, Italy). - Guarrera, Paolo Maria; Salerno, Giovanni; Caneva, Giulia (Journal of ethnopharmacology, 2005)
Field ethnobotanical survey was undertaken for the period of 2002-2003 in the Tyrrhenian part of the Basilicata region of southern Italy. Data of 56 species of plants belonging to 29 families where gathered through interviews; among the species, 47 are used in human therapy, 6 as insect repellents, 15 in veterinary medicine, 1 for its ichthyotoxic properties and 3 for magic therapeutic purposes. The most important findings in ethnomedicine relate to Nasturtium officinale (renal colic, liver diseases), Foeniculum vulgare subsp. piperitum (mouth ulcers), Leopoldia comosa (toothache, headache), Micromeria graeca subsp. graeca (coughs) and Ceterach officinarum (malaria), while in the ethnoveterinary field, we have Pteridium aquilinum (wolf bites) and Spartium junceum (fractures of animal limbs).
Keywords: Abdominal Pain; Abdominal Pain: drug therapy; Anthelmintics; Anthelmintics: therapeutic use; Antiparasitic plants; Basilicata; Common Cold; Common Cold: drug therapy; Cough; Cough: drug therapy; Diuretics; Diuretics: chemistry; Diuretics: therapeutic use; Ethnobotany; Ethnopharmacology; Ethnopharmacology: methods; Furunculosis; Furunculosis: drug therapy; Geography; Humans; Italy; Lung Diseases; Lung Diseases: drug therapy; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plant Preparations; Plant Preparations: therapeutic use; Plants; Skin Diseases; Skin Diseases: drug therapy; Time Factors; Traditional; Veterinary plants; Wound Healing; Wound Healing: drug effects; Wounds and Injuries; Wounds and Injuries: drug therapy

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
The following values have no corresponding Zotero field: accession-num: 16182861
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors